2019
DOI: 10.1159/000501275
|View full text |Cite
|
Sign up to set email alerts
|

Differential Organ-Specific Tumor Response to Immune Checkpoint Inhibitors in Hepatocellular Carcinoma

Abstract: <b><i>Background and Aims:</i></b> Immune checkpoint inhibitors (ICIs) exhibit significant clinical activity in patients with advanced hepatocellular carcinoma (HCC). This study explored whether tumor response to ICIs in HCC varies among different organs. <b><i>Methods:</i></b> We reviewed the data of patients with advanced HCC who had received ICIs. Patients with measurable diseases were enrolled. Organ-specific response criteria, adapted from RECIST 1.1 and imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
80
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(94 citation statements)
references
References 39 publications
11
80
2
1
Order By: Relevance
“…The link between expression of YIF1B and malignancy progression and recurrence in LIHC patients was consistent in different databases. Although much more information on the molecular role of YF1B in immune regulation is required to understand the strong correlation between YIG1B expression and LIHC, the liver is a highly metabolic organ with a different immune microenvironment, and more recent studies have described it as an immune suppressive organ [36,37]. In our results, YIF1B expression is highly related to immune cell infiltration in LIHC, as well as TMB, the MMR gene and methylation transferase expression.…”
Section: Discussionsupporting
confidence: 59%
“…The link between expression of YIF1B and malignancy progression and recurrence in LIHC patients was consistent in different databases. Although much more information on the molecular role of YF1B in immune regulation is required to understand the strong correlation between YIG1B expression and LIHC, the liver is a highly metabolic organ with a different immune microenvironment, and more recent studies have described it as an immune suppressive organ [36,37]. In our results, YIF1B expression is highly related to immune cell infiltration in LIHC, as well as TMB, the MMR gene and methylation transferase expression.…”
Section: Discussionsupporting
confidence: 59%
“…In 90 patients with advanced malignancies (mostly melanoma and GI tumors) treated with CPIs in Phase I trials, the presence of liver metastasis was significantly associated with shorter OS, PFS, and lower rate of clinical benefit (204). In a retrospective review of 75 patients with advanced HCC, ORRs in the liver, lung, lymph node, and other intra-abdominal metastases were 22%, 41%, 26%, and 39%, respectively (207). Together, these clinical data suggest that hepatic metastases may be less responsive to CPIs than extrahepatic lesions.…”
Section: Liver Metastasesmentioning
confidence: 99%
“…However, the specific immune genetic changes in HCC have not been extensively studied, although one study found that the levels of immune cells infiltration, specifically by T-cells, cytotoxic cells, Th2 cells and macrophages, in HCC were associated with improved survival in patients based on n silico analysis, suggesting that the type of immune cells present in HCC tissues were different from the immune cell profile of the normal liver (15). As the liver is now considered to a 'immune associated organ', the presence of immune cells in HCC should be taken into consideration as a leading factor for predicting prognosis following resection, and should not be restricted to specific types of immune cells (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%